Language and Gender: Analyzing Male and Female Speech in a Debate Setting - Ma, Cynthia; Rahma, Alya Vania; Septiandri, Muhammad Rizky; Rangkuti, Rahmadsyah (Universitas Muhammadiyah Mataram, 2024)
Gender and language is a topic that continues to be relevant among scholars. This study examines the influence of gender on communication styles in a debate uploaded on Youtube titled “Can 25 Liberal College Students Outsmart 1 Conservative? (feat. Charlie Kirk)”. The research is guided by Deborah Tannen’s theory of report talk and rapport talk. This research focuses solely on the first premise about abortion. The participants include five female and three male students, along with Charlie Kirk. Qualitative content analysis was used, with the dialogues transcribed and manually coded. The results align with the generalization that men often use report talk, while women lean toward rapport talk. However, the findings also reveal that both genders can switch styles depending on the situation. This study highlights the role gender plays in shapping communication strategies during debates. Although the sample size and analysis duration are limited, the findings offer valuable insights into gender communication in formal settings.